Effective and Sustainable Hydraulic Fracturing 2013
DOI: 10.5772/56373
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and Accurate Approach for Studying the Heat Extraction from Multiple Recharge and Discharge Wells

Abstract: In order to understand the thermal recovery Behavior of an engineered geothermal system (EGS), this paper develops a model in which fluid circulates in a single, planar hydraulic fracture with a constant hydraulic aperture via multiple recharging and discharging wells. The coupled equations for heat convection in the fracture plane and heat transfer into the rock are provided for steady and irrotational fluid flow conditions. By using velocity potentials and streamline functions, the temperature along a stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Gringarten and Sauty [28] used theoretical research methods to study the thermal energy extraction of geothermal systems with uniform regional flow, but Schulz [21] found that this calculation method is too cumbersome and inefficient. Rodemann [29], Heuer [30], and Wu et al [31] studied dual wells and multi-well systems, but they did not consider the effects of regional flows. Wu et al [32] used a theoretical research method to establish a two-dimensional semi-analytical model, they studied the influence of regional flow on geothermal system thermal mining, and studied well location optimization in the presence of regional flow in EGS reservoirs, but its application model is simple, it can't better reflect the real complex reservoir situation.…”
Section: Introductionmentioning
confidence: 99%
“…Gringarten and Sauty [28] used theoretical research methods to study the thermal energy extraction of geothermal systems with uniform regional flow, but Schulz [21] found that this calculation method is too cumbersome and inefficient. Rodemann [29], Heuer [30], and Wu et al [31] studied dual wells and multi-well systems, but they did not consider the effects of regional flows. Wu et al [32] used a theoretical research method to establish a two-dimensional semi-analytical model, they studied the influence of regional flow on geothermal system thermal mining, and studied well location optimization in the presence of regional flow in EGS reservoirs, but its application model is simple, it can't better reflect the real complex reservoir situation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to extracting heat from the reservoir by fluid circulation, the closed-loop system can prevent contaminants in fluids from leaking into the reservoir. As the output performance, including temperature 2 Geofluids and thermal power, of a geothermal reservoir is affected by many factors such as number and location of wells and fractures, flow rates, and velocity and direction of areal flow [6,7], an efficient mathematical model is required for studying the relationship between reservoir performance and these parameters depending on specific system configuration.…”
Section: Introductionmentioning
confidence: 99%